2009
DOI: 10.1007/s00418-009-0582-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential membrane redistribution of P2X receptor isoforms in response to osmotic and hyperglycemic stress in the rat lens

Abstract: P2X(1, 2, 3, 4, 6 and 7) are all expressed in a differentiation-dependent manner in the rat lens. However, in the lens outer cortex the subcellular distribution of all P2X isoforms is predominantly associated with a pool of receptors located in cytoplasmic vesicles. Here we investigate whether osmotic and hyperglycemic stress can alter the subcellular distribution of this cytoplasmic pool of P2X receptors. We show that in a discrete zone of the deeper outer cortex an isoform and stimulus-specific shift in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Interestingly, a large fraction of the TMEM16A channels were present as a cytoplasmic pool within the newly elongating fiber cells. It is conceivable that these channels would be dynamically redistributed to the plasma membrane in response to mechanic stress or changes in lens volume, as has been previously reported to occur for P2X receptors in the lens 22. Taken together, our electrophysiologic and cell biologic studies suggest that native lens Ca 2+ -activated Cl − channels are made up of homomeric and/or heteromeric channels composed of TMEM16A and TMEM16B.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, a large fraction of the TMEM16A channels were present as a cytoplasmic pool within the newly elongating fiber cells. It is conceivable that these channels would be dynamically redistributed to the plasma membrane in response to mechanic stress or changes in lens volume, as has been previously reported to occur for P2X receptors in the lens 22. Taken together, our electrophysiologic and cell biologic studies suggest that native lens Ca 2+ -activated Cl − channels are made up of homomeric and/or heteromeric channels composed of TMEM16A and TMEM16B.…”
Section: Discussionsupporting
confidence: 73%
“…In this regard, we have previously shown that members of the P2X family of ATP-gated NSC channels are expressed in the lens (20). Interestingly, in immunocytochemical mapping experiments the majority of these P2X channels (P2X 1,3,4,6,7 ) were shown to be localized to the cytoplasm of fiber cells, but upon hypertonic challenge a subset of the P2X channels (P2X 1,4 ) were inserted into the plasma membrane of fiber cells located in a distinct zone of the lens (37,38). This zone was some 15 cells layers in from the lens periphery, and we have previously shown that fiber cells isolated from this zone are longer than 150 m (42), cells in the current study ranged from 150 -350 m in length.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, diVerential expression of P2X receptors 2, 4, 5 and 6 on vasopressin-and oxytocin-containing neurons in supraoptic and paraventricular nuclei of rat hypothalamus was 123 described ). In the rat lens, diVerential membrane redistribution of P2X receptor isoforms in response to osmotic and hyperglycemic stress was found by Suzuki-Kerr et al (2009). In response to hypertonic stress, P2X1 and 4 became more closely associated with the broad sides of Wber cells, whereas under hypotonic conditions P2X4 and 6 associated with the narrow side membranes.…”
Section: Central Nervous Systemmentioning
confidence: 94%
“…Several recent studies examined the distribution of purinoreceptors in diVerent neurons (Banerjee et al 2009;Guo et al 2009;Kestler et al 2009;Suzuki-Kerr et al 2009). Two major families of purinoceptors have been identiWed as P1 and P2, respectively (Nakatsuka and Gu 2006).…”
Section: Central Nervous Systemmentioning
confidence: 99%